A representação feminina nos romances de Cyro dos Anjos - Geuvana Vieira de Oliveira (2011)
This research analyses the way female characters are portrayed in O amanuense Belmiro, Abdias and Montanha, by Cyro dos Anjos, observing what happens according to their narrators, the representation of these figures that present traditional and modern stereotypes. The traditional characters that make up the corpus are drawn from each of these novels, and Emily, Charlotte and Claudia figures who act contaminated by traces of attitudes linked to a sociocultural tradition. In contrast, we examine also the modern characters Jandira, Gabriela and Anna Maria, which are built with aspects of the modern woman. Theoretical resource, we use theoretical and critical texts on the historical and cultural context of colonial Brazil until the twentieth century, in order to understand the social conventions and figuration of the characters that simulate certain behaviors that social structure.